Penerapan Metode Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Belajar Matematika - Azisa, Riskatul; Nurhusmah, Nurhusmah; Fauziah Amruh, Afifah (Green Publisher Indonesia, 2025)
This research aims to investigate the application of project-based learning (PJBL) methods in improving student mathematics learning outcomes. Project-based learning is considered effective for improving critical thinking skills, creativity, and a deeper understanding of mathematical concepts. This method involves students actively in the learning process through project activities designed to develop an in-depth and contextual understanding of mathematical concepts. The research method uses literature studies involving the procces of finding data or research information through reading scientific journals, reference books, and other published materials available in the library, after relevant sources are collected, a thorough analysis is carried out to understand the results of related research. Student mathematices involves analyzing and collecting data from various relevant literature sources. The results of the study indicate that the application of PJBL can significantly improve students’ mathematics learning outcomes. Project Based Learning/PJBL has proven to be effective in improving student learning outcomes, especially in subjects such as mathematices. The method encourages students to understand concepts in depth directly and complete relevant projects.